Optimization of White Oyster Mushroom (Pleurotus ostreatus) Growth Using Various Media Enriched with Millet Flour - Suherman; Muttaqin, Zainul; Rahim, Iradhatullah; Zamzam, Syamsiar (Edupedia Publisher, 2024)
This study aims to evaluate the best growing medium for the mycelium growth of F1 oyster mushroom (Pleurotus ostreatus) seeds using millet flour as a nutritional supplement. A Completely Randomized Design (CRD) was applied with two factors: the type of growing medium (corn, sawdust, rice husks) and the concentration of millet flour (0%, 25%, 50%, 75%). Observed variables included mycelium growth (cm), mycelium density, and daily growth on the 7th, 14th, and 21st days after inoculation. The results indicated that corn without millet flour (J1P0) produced the best mycelium growth, while adding 25% millet flour to corn (J1P1) and sawdust (J2P1) enhanced mycelium density. However, higher millet concentrations (50% and 75%) tended to reduce growth efficiency due to excessive moisture content. This study recommends using millet flour at low concentrations to improve the efficiency of sustainable F1 oyster mushroom seed production.